APPRAISAL OF COMPLEMENTARY AND ALTERNATIVE MEDICINE UTILIZATION AMONG DOCTORS FOR THEIR WEIGHT REDUCTION: A PILOT SURVEY - SAKSHI SINGH; ARVIND KUMAR YADAV; MEENU PICHHOLIYA; SANGITA GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: To study appraisal of complementary and alternative medicines (CAM) utilization among doctors for their weight reduction. Methods: This present cross-sectional, questionnaire-based observational study was conducted in Department of Pharmacology of a tertiary care teaching hospital of Rajasthan, India. All the doctors of various specialties were included in the study. The validated questionnaire had three separate segments consisting of items regarding demographic profile, items regarding knowledge of CAM and items regarding CAM utilization by the medical professionals. Results: Out of total 222 respondents, 63(28%) doctors used CAM for their weight reduction. 19(8.6%) male and 44(19.8%) female doctors used CAM for weight reduction. CAM practice among the postgraduate doctors was highly significant in comparison to other qualifications (p<0.001). Association between clinical years of practice and use of CAM was found to be significant (p<0.05). CAM use with respect to body mass index (BMI) of doctors was found statistically significant (p<0.001). 183(82%) doctors were aware of the term CAM and 144 (65%) believed in CAM. Conclusion: This study concluded that 28% doctors had used CAM for themselves for weight reduction. A substantial number of doctors are using CAM themselves and also recommending to others in spite of being trained in modern medicine.